"Ustvarjalni duh metafizične naravnanosti" - Bergamo, Marija (Muzikološki zbornik, 2008)
In memoriam Uroš Krek (1922-2008), a classic of newer Slovene music and composer of an extensive as well as precious orchestral, chamber, piano, and choral output, discusses bases and premises regarding his composing. It analyses the spiritual axis his strategic decisions that conditioned the physiognomy of his compositional technique. Conditionally, the article gives him a place in the sphere of neoclassical ludism and the autonomy of music, atthe same time dealing with the composer's relation to modernism, novelties and tradition, and to the historical and folk music heritage.
Keywords: aesthetics; estetika; kompozicija; Krek, Uroš, 1922-2008; skladatelji